Early prosthodontic intervention in a child patient of hypohidrotic ectodermal dysplasia - Culatur Thulasingam; Meenakshi Akshayalingam; Pallavi Vashisht (SRM Journal of Research in Dental Sciences, 2013)
The ectodermal dysplasias (EDs) comprise a large, heterogeneous group of inherited disorders that are defined by primary defects in the development of two or more tissues derived from embryonic ectoderm. Patients with this disease often need complex prosthetic treatment. The physiologic and psychosocial value of prosthetic dental treatment increases all the more in very young patients, in which absence of teeth can negatively affect psychological and social growth of child. This clinical report describes the prosthetic management of a 4-year-old child patient with ED.